The Effect of Accounting Information Systems, Internal Control, and Organizational Culture on Company Performance - Sari, Evi Novita; Syaiful (Indonesian Vocational Research Journal, 2025)
This investigation endeavors to delve into how Accounting Information Systems (AIS), mechanisms of Internal Control, and the prevailing Organizational Culture influence the overall effectiveness of corporate operations. Centered on PT Semen Indonesia Logistik, the study engaged 54 carefully chosen participants through purposive sampling, ensuring alignment with the research objectives. Data was gathered using a structured questionnaire employing the Likert scale, while analysis was conducted via multiple linear regression, supported by SPSS version 26 software. The findings underscore that AIS and Internal Control significantly shape corporate performance. This indicates that a well-integrated digital accounting framework, coupled with disciplined oversight systems, can propel operational accuracy, bolster accountability, and accelerate goal attainment. In contrast, Organizational Culture did not emerge as a statistically impactful factor—likely attributed to its insufficient integration into the day-to-day rhythm of business conduct. These insights call upon company leadership to deepen their reliance on technological systems and fortify internal controls, while simultaneously re-evaluating their cultural assimilation strategies. This research aims to serve as a guiding reference for shaping policies related to performance optimization and strategic resource governance within contemporary organizational structures.